2018
DOI: 10.1016/j.biocel.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

MiR-155-5p inhibits PDK1 and promotes autophagy via the mTOR pathway in cervical cancer

Abstract: Cervical cancer is one of the most common malignant tumors and the leading cause of cancer-related mortality in women. Persistent cervical infection by high-risk human papillomavirus (hrHPV) is related to cervical cancer. MicroRNAs could regulate autophagy caused by viral infection. The aim of the present study was to investigate the regulation of autophagy by miR-155-5p in cervical cancer. In HPV+ human cervical lesion tissues, miR-155-5p expression was found to be markedly decreased. Compared to C33A cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 24 publications
2
42
0
Order By: Relevance
“…miR‐155‐5p is a multifunctional miRNA, which can regulate the pathophysiological processes, such as inflammation, angiocardiopathy, and carcinogenesis . miR‐155 can suppress the progression of gastric cancer and promote autophagy via the mTOR pathway in cervical cancer . In lung cancer cells, miR‐155‐5p can suppress the migration and invasion of cancer cells via targeting Smad2 .…”
Section: Discussionmentioning
confidence: 89%
“…miR‐155‐5p is a multifunctional miRNA, which can regulate the pathophysiological processes, such as inflammation, angiocardiopathy, and carcinogenesis . miR‐155 can suppress the progression of gastric cancer and promote autophagy via the mTOR pathway in cervical cancer . In lung cancer cells, miR‐155‐5p can suppress the migration and invasion of cancer cells via targeting Smad2 .…”
Section: Discussionmentioning
confidence: 89%
“…Dysregulation of this process contributes to tumor progression [13]. Autophagy, which is lower in cancerous than in normal cells, has been observed in malignant cells and cells with malignant potential [72]. An evaluation of the levels of miR155 in cervical and nasopharyngeal cancer shows that if members of the mTOR pathway (RHEB, RICTOR and RPS6KB2) are activated, the levels of miR155 are lowered and autophagy is decreased.…”
Section: Hypoxic Modulation Of Carcinogenesis Via Mtor Signalingmentioning
confidence: 99%
“…Recently, the involvement of miRNAs in tumorigenesis and their signi cance as effective biomarkers are also becoming increasingly appreciated [14]. miR-155-5p has been found to regulate the development of various cancer types, including human epithelial ovarian cancer [16], cervical cancer [17,18], and colon cancer [19]. It has been reported that some certain long non-coding RNAs (lncRNAs) suppress HCC development by sponging miR-155-5p [20]; miR-155-5p modulated the malignancy of HCC by regulating Wnt/β-catenin signaling or suppressing PTEN through the PI3K/Akt pathway [21,22]; therefore, miR-155-5p can be a promising therapeutic target for HCC patients.…”
Section: Discussionmentioning
confidence: 99%